Systemic Sclerosis-associated Pulmonary Arterial Hypertension - Le Pavec, Jérôme (American Thoracic Society, 2010)
Pulmonary arterial hypertension (PAH) is a devastating vascular complication of a number of connective tissue diseases, including systemic sclerosis (SSc), where it has a dramatic impact on the clinical course and overall survival and is the single most common cause of death in patients afflicted with this syndrome. Although remarkable advances have been achieved in elucidating the pathogenesis of PAH over the past 2 decades, leading to the development of disease-targeted therapies for the idiopathic form of this condition (IPAH), the response to therapy is suboptimal in SSc-related PAH (SSc-PAH), and survival remains very poor. Factors accounting for striking clinical and prognostic differences between these two syndromes are unclear but may include a more pronounced autoimmune, cellular, and inflammatory response, and a higher prevalence of comorbidities in SSc-PAH, including cardiac and pulmonary venous and parenchymal involvement. Furthermore, currently available markers of disease severity and clinical tools to assess response to therapy, which may be reliable in IPAH, are either limited or lacking in SSc-PAH. Thus, a more focused approach, including a better understanding of the pathogenesis and genetic factors underlying the development of SSc-PAH, a search for more specific and reliable tools to adequately assess functional impairment and monitor therapy, as well as the design of novel targeted therapies, are all urgently required to alter the dismal course of this syndrome.